Future Positive: International Co-operation in the 21st Century - Edwards, Michael (Routledge, 1999)
An optimistic assessment of the prospects for a new international order - acting as a counter-blast to global pessimism. The text explains how the international system operates, the pressures it faces and the changes it must undergo, and offers concrete ideas to re-frame international relations, foreign aid and humanitarian intervention, without using jargon or simplistic judgements.